The importance of joint line obliquity: a radiological analysis of restricted boundaries in normal knee phenotypes to inform surgical decision making in kinematically aligned total knee arthroplasty - MacDessi, Samuel J.; Allom, Richard J.; Griffiths-Jones, Will; Chen, Darren B.; Wood, Jil A.; Bellemans, Johan (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2022)
Purpose Restricted kinematic alignment (rKA) in total knee arthroplasty (TKA) aims to restore native soft tissue laxities while limiting alignment extremes that risk prosthetic failure. However, there is no consensus where restricted boundaries (RB) should be set. This study aims to determine the proportion of limbs in which constitutional alignment and joint line obliquity (JLO) would be restored with various RB scenarios, to inform decision making in rKA TKA. Methods The mechanical hip–knee–ankle (mHKA) angle, arithmetic hip–knee–ankle (aHKA) angle, lateral distal femoral angle (LDFA) and medial proximal tibial angle (MPTA) were measured on radiographs of 500 normal knees. Incrementally wider RBs were then applied. The proportion of limbs within each increment was determined when RBs were applied only to HKA, or to HKA, LDFA and MPTA together. In addition, the proportion of limbs within published adjusted mechanical alignment (aMA) and rKA protocols were determined, as well as those within one, two and three standard deviations of the means for HKA, LDFA and MPTA. Results When restrictions to mHKA alone were applied, 74.0% and 97.8% of knees were captured with boundaries of ± 3° and ± 6° respectively. However, when the same boundaries to HKA were also applied to MPTA and LDFA, 36.2% and 91.0% of knees were captured respectively, highlighting the limiting effect that JLO has on restoration of normal knee phenotypes. When comparing previously published boundaries, aMA of 0° ± 3° captured 36.2%; rKA of 0° ± 3 for HKA and 85° to 95° for LDFA/MPTA captured 67.8%; rKA of − 5° to 4° HKA and 86°–93° for LDFA/MPTA captured 63%; and rKA of − 6° to + 3° for HKA and 84°–93° for LDFA/MPTA captured 85.4%. Conclusion The greatest proportions of normal knee phenotypes were captured with boundaries that were centred around population means for HKA and JLO. Further, these findings demonstrate that restricting the JLO has a significant limiting influence on restoration of normal knee phenotypes beyond that of restricting HKA alone. Level of evidence III.